Dissemination of the Application of Law on Online Buying and Selling on the Shopee Application Review of Fiqh and the Civil Code to Prospective Customers - Roni Ade Irawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This devotional article describes legal socialization of buying and selling online on the fiqh review shoope application and the Civil Code to prospective customers. The purpose of this service is education and advocacy to the reading public that buying and selling in modern times is not only done face to face but can be done online based on the use of technology. The type of service for this article is a qualitative legal service that seeks to explain and describe a portrait of the author's dedication in disseminating legal views to prospective customers and then describe it by following the guidelines for scientific writing. Invitations that apply are in accordance with the Civil Code Articles 1457 and Article 1458. Because with this basis, it is expected that sellers and buyers make buying and selling transactions properly and in accordance with the rules that apply so that fraud and fraud can also be minimized so that sales can be carried out without distance constraints and purchases also become safer. Second, if there is a delay, the parties involved/involved must immediately confirm so that there are no misunderstandings in the transaction. Third, parties who are bound/involved must act responsibly, especially for business actors who may take advantage of buying and selling, but the rights of buyers must still be respected in accordance with the principles of Islamic business ethics